Characterization and application of moisturizer in skin treatment: A review: Moisturizer in Skin Treatment - Ainurofiq, Ahmad; Arfa Fairuziyah Firdausy Divinda Haya; Asifa Nurma Safitri; Ika Zuliana Solihatin; Safna Bina Nusriya; Tasya Saevita Nugroho (Journal of Pakistan Association of Dermatologists, 2023)
Repeated exogenic exposure can disrupt the skin barrier in maintaining the water level and lipid disruption in the stratum corneum to trigger transepidermal water loss (TEWL), leading to scaly, dull, itchy, and more sensitive skin. The skin also contains a natural moisturizer, known as the natural moisturizing factor (NMF). However, if there is inadequate NMF to maintain skin moisture, additional protection is needed using cosmetics moisturizers. A moisturizer is a product aimed to increase skin hydration and maintain normal skin pH. Moisturizer is classified as occlusive, humectant, and emollient moisturizers with different work mechanisms. Although reports on the risks of moisturizer are rare, moisturizer can cause xerosis and positively modifies the skin barrier. Other harmful reactions for the skin include sensory reactions, such as pain, burning sensation, and sting on sensitive facial skin. Therefore, the ingredients in moisturizers need to be considered to prevent toxicity or adverse effects. This review aims to evaluate published studies on cosmetics, advantages, disadvantages, and characterization of moisturizers. The characteristics discussed in this review include organoleptic/light test, pH determination, stability, spreadability, saponification value, density, viscosity, homogeneity, irritability, in vitro, in vivo, and in vivo skin hydration.